Removing copper, chromium and nickel in industrial effluent using hydroxide precipitation versus sulphide precipitation / Siti Rohana Mohd Yatim ... [et al.] - Mohd Yatim, Siti Rohana; Kasmuri, Siti Nor Hazliyana; Syahjidan, Hanin Nazhifah; Mokhtar, Nurul Shahirazni; Zainuddin, Nur Ain (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Rapid growth of industries, such as the electroplating industry has led to large scale water pollution, due to the release of wastewater containing high concentration of heavy metals such as chromium (Cr), copper (Cu) and nickel (Ni) that does not comply with the Industrial Effluent Regulation (IER) 2009. This experiment was conducted to determine the efficiency of removal heavy metals by using hydroxide precipitation and sulphide precipitation. The optimum condition, which is pH and coagulant dosage were determined by jar test. Jar test was conducted on two different types of chemical precipitation, which is hydroxide precipitation using sodium hydroxide (NaOH) and sulphide precipitation using sodium sulfide (Na2S). The result shows the optimum condition of removal Cr, Cu and Ni in hydroxide precipitation was at pH 8.5 while for sulphide precipitation was at pH 10. The optimum coagulant dosage (ferric chloride = FeCl) for hydroxide precipitation and sulphide precipitation was 0.8 mL. For hydroxide precipitation, Cr = 98.65%, Cu = 2.81% and Ni = 99.90% were removed while for sulphide precipitation Cr = 91.29%, Cu = 99.99% and Ni = 99.97%. From the results, it showed that sulphide precipitation was more effective to remove Cr, Cu and Ni compared to hydroxide precipitation as it can remove heavy metals at broad range of pH.